Fiscal Policies in High Debt Euro-Area Countries - Cavallo, Antonella (Springer International Publishing, 2018)
This book explores the role of national fiscal policies in a selected group of Euro-area countries under the European Economic and Monetary Union (EMU). In particular, the authors characterize the response of output to fiscal consolidations and expansions in the small Euro-area open economies affected by high public and private debt. It is shown that the macroeconomic outcome of fiscal shocks is strongly related to debt levels. The Euro-area countries included in the investigation are Greece, Ireland, Italy, the Netherlands, Spain, and Portugal, over the sample period 1999-2016, i.e., the EMU period. The main econometric tools used in this research are structural vector autoregressive (VAR) models, including panel VAR models. The available literature relating to the subject is also fully reviewed. A further closely investigated topic is the potential spillover effects of German fiscal policies on the selected small Euro-area economies. Moreover, in the perspective of the evolution of the Euro Area towards a full Monetary and Fiscal Union, the authors study the effects of area-wide government spending shocks on aggregate output and other macroeconomic variables during the EMU period. The closing chapter of the book considers evidence on the consequences of austerity policies for European labour markets during recent years.